Exploring Tryptophan-based Short Peptides: Promising Candidate for Anticancer and Antimicrobial Therapies - Rai, Neha; Tiwari, Richa Tripathy; Sahu, Adarsh; Verma, Ekta; Rathore, Swati; Patil, Shailendra; Patil, Asmita Gajbhiye (Anti-Cancer Agents in Medicinal Chemistry, 2025)
BackgroundUltra-short peptides are essential therapeutic agents due to their heightened selectivity and reduced toxicity. Scientific literature documents the utilization of dipeptides, tripeptides, and tetrapeptides as promising agents for combating cancer. We have created a range of tryptophan-based peptides derived from literature sources in order to assess their potential as anticancer drugs.MethodsWe present the results of our study on the antibacterial and anticancer effectiveness of 10 ultra-short peptides that were produced utilizing microwave-assisted solid phase peptide synthesis. The synthesized peptides underwent screening for in vitro antibacterial activity using the agar dilution method.ResultsHPLC, LC-MS, 1H NMR, and 13C NMR spectroscopy were used to analyze the synthesized peptides. In tests using the HeLa and MCF-7 cell lines, the synthesized peptides' anticancer efficacy was assessed. The study found that two peptides showed potential median inhibitory concentration (IC50) values of 3.9±0.13 µM and 1.8±0.09 µM, respectively, and showed more activity than the reference medication doxorubicin.ConclusionThe antibacterial activity of synthesized peptides 3b and 4b was found to be better than the other synthetic peptides. MIC value of roughly 5–50 µg/mL for peptides 3a, 4c, and 4d showed strong antifungal activity against Candida albicans. The synthesized peptides were also evaluated for their anticancer activity against HeLa and MCF-7 cell lines, and found that peptides 3e and 4e were more potent than other peptides against doxorubicin.
Keywords: Solid phase peptide synthesis